126 Cost Utility of Serial Computed Tomography Angiography vs Magnetic Resonance Angiogram for Small, Unruptured, Internal Carotid Artery Aneurysms: Are Either Worth It?. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Fusco, Matthew; Thomas, Ajith J.; Reddy, Suresh A.; Ogilvy, Christopher S.
Abstract: INTRODUCTION: An increasing number of unruptured aneurysms are being detected as the quality and utilization of imaging modalities expands. Often these aneurysms are small and located within the cavernous or pre-communicating internal carotid artery (ICA). Treatment is typically withheld for these aneurysms and some pattern of serial follow-up imaging is undertaken via either computed tomography angiography (CTA) or magnetic resonance angiogram (MRA). It is currently not clear if either of these options provides a cost-effective method of surveillance. This study aims to quantify the price and utility of these follow-up imaging strategies. METHODS: A literature review of rupture and growth rates for aneurysms <5 mm in the cavernous or paraclinoid ICA was undertaken. Various reports of payment amounts for CTA or MRA were collected. Using this information a decision analysis for cost utility of CTA or MRA was created to determine the expenditures involved in detecting aneurysmal growth to a size that may require treatment (ie, >5 mm). RESULTS: Reported rupture rates of ICA aneurysms <5 mm range from 0.0% to 0.14%. Growth rates for these aneurysms vary from 0.00 to 0.31 mm/year in 1.0% to 6.9% of followed lesions. The average insurance company payment in the United States for a head CTA is $6200 (range $1500 in Redding, California to $10, 700 in Bishop, California) and $3300 for a brain MRA (range $500 in Auburn, Indiana to $10, 800 in Dyersburg, Tennessee). CONCLUSION: Small cavernous or paraclinoid ICA aneurysms demonstrate low rates of rupture or growth. Serial imaging with either CTA or MRA to follow these lesions is expensive. The cost of these studies often varies considerably depending on the geographic region, but MRA is, on average, cheaper than CTA. A decision analysis with cost-utility information will stratify the expenditures necessary to follow these aneurysms over varying rupture and growth rates as well as imaging prices.